Training Mediated by Organizational Culture and Moderated by Organizational Commitment and Leadership as Control Variables - Sjarifudin, Didin; Wahdiniawati, Siti Annisa; Untari, Dewi; Sidjabat, Sonya; Basuki, Carola (Dinasti Publisher, 2024)
The purpose of this research article is to find out whether there is an influence between variables in this study. This study used a quantitative research approach. The population consisted of 65 supervisors, whose online questionnaire was distributed to several manufacturing companies in Jababeka in January – February 2024, resulting in 65 responses. The sample size remains 65 supervisors. The collected data was analyzed through multiple regression analysis using SEM PLS series 4. Before conducting data analysis, several tests were carried out to determine the significance between variables both individually and simultaneously. Leadership is more instrumental in shaping organizational commitment than training. Therefore, companies need to pay attention to leadership development as one of the strategies to increase the level of employee commitment to the organization.